NURSING AND BREASTFEEDING: HEALTH EDUCATION STRATEGIES IN ROUTINE RISK PRENATAL CARE - Gomes, Barbara Santana; Santos, Francinne de Souza; Azzolin, Gabriela Carmo Marchiori; Espinace, Isabela; Silva, Isadora de Lima; Brandolin, Maria Eduarda Oliveira; Marques, Maria Luísa Sousa Severo; Góes, Yara Maria Randi (Seven Editora, 2026)
Exclusive breastfeeding is recognized as one of the most effective strategies for promoting child health and reducing morbidity and mortality in the first months of life. However, the rates of this practice still remain below public health targets, highlighting the need for the implementation of strategies that encourage, support, and strengthen exclusive breastfeeding. In this context, the role of the nurse during prenatal care stands out as a fundamental element for the development of educational actions aimed at promoting breastfeeding. The present chapter aims to analyze the role of nursing in health education, carried out during prenatal follow-up as a strategy to promote and strengthen exclusive breastfeeding. This is an integrative literature review conducted in scientific databases and relevant institutional sources in the health field.The results show that educational actions carried out by the nurse, such as dialogued consultations, groups of pregnant women, and home visits, contribute significantly to strengthening maternal self-confidence and preventing early weaning. It is concluded that health education conducted during prenatal care constitutes an essential tool to increase adherence to exclusive breastfeeding and to strengthen women’s autonomy in the breastfeeding process.